Prevalence of Multiple Drug-Resistant Bacteria Among Healthcare Acquired Infections in the WHO Eastern Mediterranean Region: A Systematic review (Asian Journal of Public Health and Nursing, 2026)
Background:Hospital-acquired infections (HAIs) caused by multidrug-resistant (MDR) bacteria represent a growing global public health threat, particularly in low- and middle-income regions such as the WHO Eastern Mediterranean Region (EMR). Despite increasing antimicrobial resistance, comprehensive regional evidence on MDR-HAIs, including prevalence, pathogen distribution, and associated risk factors, remains limited. This systematic review aimed to examine the prevalence of MDR bacteria among HAIs in hospitalized patients across the EMR between 2014 and 2024. Methods:A systematic review was conducted following Cochrane guidelines. EMBASE, PubMed, and Google Scholar were searched using Medical Subject Headings (MeSH) and relevant keywords. Eligible studies included primary quantitative studies reporting MDR hospital-acquired infections in EMR countries. A total of 550 records were identified, and after screening, critical appraisal, and eligibility assessment, nine studies were included for narrative synthesis. Risk of bias was assessed using CASP and Joanna Briggs Institute appraisal tools. Results:The prevalence of MDR-HAIs across EMR countries ranged from 4.9% to 52.6%, with most studies reporting rates exceeding 25%. Egypt reported the highest prevalence (52.6%), followed by Libya (35.2%) and Lebanon (30.2%), while Iraq reported the lowest prevalence (4.9%). Older age and male gender were commonly associated with increased MDR-HAI risk. The most frequently identified pathogens were MDR Pseudomonas aeruginosa, extended-spectrum beta-lactamase (ESBL) Klebsiella pneumoniae and Escherichia coli, multidrug-resistant Acinetobacter baumannii, and methicillin-resistant Staphylococcus aureus (MRSA). Additional risk factors included comorbidities, prolonged hospitalization, prior antibiotic exposure, invasive devices, and admission to high-risk wards. Conclusion:MDR hospital-acquired infections remain highly prevalent across the EMR, affecting countries regardless of economic status. Strengthening surveillance systems, improving infection prevention and control strategies, and implementing coordinated antimicrobial stewardship programs are urgently needed to reduce MDR burden and improve patient outcomes in the region.